2016
DOI: 10.1021/jacs.6b11190
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Boron-Derived Radicals with Nucleophiles

Abstract: Reactions of phenanthrenedione- and pyrenedione-derived borocyclic radicals, CHOB(CF) (n = 14 (1), 16 (3)), with a variety of nucleophiles have been studied. Reaction of 1 with P(t-Bu) affords the zwitterion 3-(t-Bu)PCHOB(CF) (5) in addition to the salt [HP(t-Bu)][CHOB(CF)] (6). In contrast, the reaction of 1 with PPh proceeds to give two regioisomeric zwitterions, 1-(PhP)CHOB(CF) (7a) and 3-(PhP)CHOB(CF) (7b), as well as the related boronic ester CHOB(CF) (2). In a similar fashion, 3 reacted with PPh to give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…The bond length of B1 (B1')-C8 (C8') (1.635(8) Å) in 2 2is considerably shorter than that in 1 2due to the formation of above plane. Notably, the central Ring B moiety has a small BLA: the C7-C8 and C8-C9' bond lengths are 1.422 (8) and 1.400(6) Å, respectively, while C7-C9 bond length is 1.403 7Å. This small BLA illustrates the aromatization of 1,4-cyclohexadiene, which is consistent with the Nucleus-Independent Chemical Shifts (NICS) calculations.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The bond length of B1 (B1')-C8 (C8') (1.635(8) Å) in 2 2is considerably shorter than that in 1 2due to the formation of above plane. Notably, the central Ring B moiety has a small BLA: the C7-C8 and C8-C9' bond lengths are 1.422 (8) and 1.400(6) Å, respectively, while C7-C9 bond length is 1.403 7Å. This small BLA illustrates the aromatization of 1,4-cyclohexadiene, which is consistent with the Nucleus-Independent Chemical Shifts (NICS) calculations.…”
supporting
confidence: 81%
“…Bourissou et al 7 displayed a Gomberg-type dimerization process of P-coordinated boryl radical (D, Scheme 1) through single-crystal X-ray diffraction. Stephan et al 8 described the reaction process of phenanthrenedione-and pyenedione-derived borocyclic radicals (E, Scheme 1), C n H 8 O 2 B(C 6 F 5 ) 2 • (n =14 or 16) with a variety of nucleophiles.…”
mentioning
confidence: 99%
“…Whereas compound 4 was routinely isolated as pale yellow‐green crystals (Scheme ), repeated attempts to isolate and characterize other side products from the thick residue were unsuccessful. Interestingly, Stephan and co‐workers recently reported that phenanthrenedione‐ (Figure d) and pyrenedione‐derived borocyclic radicals exhibit unique reactivity with nucleophiles (phosphines, carbenes, amines, and pyridines) …”
Section: Figurementioning
confidence: 99%
“…The C(2)−C(3) bond in 4 [1.365(2) Å] compares well with reported imidazole C=C double bonds . The four‐coordinate boron atom in 4 exhibits a 11 B NMR resonance at δ =18.9 ppm, which is comparable to the values reported for the zwitterions containing dioxoborocyclic moieties ( δ =10.2–11.1 ppm) . While comparing well to those [1.732(4)– 1.737(2) Å] in carbene‐stabilized sulfenyl cations, the C(1)−S(1) bond in 4 [1.7256(18) Å] is about 0.09 Å longer than that in 3 .…”
Section: Figurementioning
confidence: 99%
“…[23] However,t reatment of agreen C 6 D 5 Br solution of 4 with two equivalents of 4-dimethylaminopyridine (NC 5 H 4 NMe 2 )i mmediately produced al ight orange solution. These species were not found to react with tBu 3 P, in contrast to the closely related borocyclic radicals, for which the nucleophilic aromatic CÀHs ubstitutionw as seen.…”
mentioning
confidence: 99%